Gender based Correlation between Hand measurement and Height in Medical Students of Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, Sindh: Gender-Based Correlation of Hand Size and Height - Ram, Hari; Talpur, Mir Ghulam Ali; Abro, Farooq Ahmed; Qayyum, Sadia Abdul; Kazi, Salman Ahmed Farsi; Qadri, Naveed Ali (Pakistan Journal of Health Sciences, 2024)
Anthropometry was an organized measurement procedure used in physical anthropology. Hand dimensions can represent an individual’s identity. Stature, a complex of linear dimensions, correlates with various body parts. Objective: To explore the gender-wise correlation between hand measurement and stature across a diverse population for estimating the stature of MBBS Medical Students of Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, Sindh. Methods: It was descriptive cross- sectional study and its sample size was calculated by using Open-epi online calculator. Non convenience sampling method adopted while collecting the data. Research invitations were extended to MBBS students of SMBBMU to participate in a research project and only 354 voluntarily agreed to participate out of which 169 (47.7%) males and 185 (52.3%) females fulfilled the inclusion criteria and written informed consent were taken before proceeding of data collection. Results: For both males and females, hand breadth measurements were strongly correlated with each other. The height of hands was also strongly correlated between left and right hands, particularly in males. Those who were involving age or overall height, were generally weaker and not always statistically significant. Males show more significant and stronger correlations between hand measurements and other variables compared to females, who have some significant but generally weaker correlations. Conclusion: The findings underscore that taller individuals generally possess larger hand dimensions, and marked differences exist in hand measurements between males and females